New free-air and Bouguer gravity fields of Taiwan from multiple platforms and sensors - Hwang, C.; Hsu, H.-J.; Chang, E.; Featherstone, Will; Tenzer, R.; Lien, T.; Hsiao, H.; Shih, H.C.; Jai, P.-H. (Elsevier Science BV, 2014)
We construct 1' × 1' grids of free-air and Bouguer gravity anomalies around Taiwan with well-defined error estimates for quality assessment. The grids are compiled from land, airborne and shipborne gravity measurements, augmented with altimeter gravity at sea. Three sets of relative land gravity measurements are network-adjusted and outlier-edited, yielding accuracies of 0.03–0.09 mGal. Three airborne gravity sets are collected at altitudes 5156 and 1620 m with accuracies of 2.57–2.79 mGal. Seven offshore shipborne gravity campaigns around Taiwan and its offshore islands yield shallow-water gravity values with 0.88–2.35 mGal accuracies. All data points are registered with GPS-derived geodetic coordinates at cm–dm accuracies, allowing for precise gravity reductions and computing gravity disturbances. The various datasets are combined by the band-limited least-squares collocation in a one-step procedure. In the eastern mountainous (or offshore) region, Bouguer anomalies and density contrasts without considering the oceanic (or land) topographic contribution are underestimated. The new grids show unprecedented tectonic features that can revise earlier results, and can be used in a broad range of applications.